Respuesta :

Answer:

The simplified equation is [tex]\pm\frac{\sqrt{b^2-4ac}}{2a}[/tex]

Step-by-step explanation:

Step 1:Applying Quotient Rule

[tex]\sqrt[n]{\frac{a}{b}}=\frac{\sqrt[n]{a}}{\sqrt[n]{b}},\:\quad \mathrm{\:assuming\:}a\ge 0,\:b\ge 0[/tex]

[tex]\pm \sqrt{\frac{b^2-4ac}{4a^2}}[/tex] = [tex]\pm \frac{\sqrt{b^2-4ac}}{\sqrt{4a^2}}[/tex]----------------------------(1)

Step 2:  Applying radical Rule

[tex]\sqrt[n]{ab}=\sqrt[n]{a}\sqrt[n]{b},\:\quad \mathrm{\:assuming\:}a\ge 0,\:b\ge 0[/tex]

[tex]\sqrt{4a^2}=\sqrt{4}\sqrt{a^2}[/tex]

So equation(1) can be written as

[tex]\pm \sqrt{\frac{b^2-4ac}{4a^2}}[/tex] [tex]= \pm \frac{\sqrt{b^2-4ac}}{\sqrt{4}\sqrt{a^2}}[/tex]-----------------------------(2)

Now

[tex]\sqrt{4} = 2[/tex]

[tex]\sqrt{a^2} = a[/tex]

Now equation(2) becomes

[tex]\pm \sqrt{\frac{b^2-4ac}{4a^2}}[/tex] =  [tex]\pm \frac{\sqrt{b^2-4ac}}{2a}[/tex]

ACCESS MORE